Supervision and Control of The Government Internal Supervisory Apparatus in The Implementation of Regional Autonomy - Engkus; Cecep Wahyu Hoerudin; Dedeng Yusuf Maolani (GoAcademica Research & Publishing, 2019)
The main problem of this regional autonomy research is the low competence of human resources in the New Autonomous Region of Pangandaran Regency, which is caused by its suboptimal implementation. The purpose of this study is to describe the implementation of regional autonomy and its impact. The method used is a qualitative approach with observation, interview and library study techniques. This study concludes that the implementation of regional autonomy in Pangandaran is not yet optimal. The positive impact of regional autonomy can increase the efficiency and responsiveness of government in public services with public preference, and arouse the spirit of competition and innovation among local governments. The negative impact, the quality of public services is low, due to the transfer of authority which is often misunderstood or misused so that adequate and formal supervision and control is needed both formally and informally as well as synergy between local, provincial and central governments.